2017
DOI: 10.1016/j.jamda.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Potentially Inappropriate Medication Use in Long-Term and Acute Care Settings: A Systematic Review

Abstract: Background Potentially inappropriate medications (PIM) are widely used in institutionalized older adults, yet the key determinants that drive their use are incompletely characterized. Methods We systematically searched published literature within MEDLINE® and Embase® from January 1998 to March 2017. We searched for studies conducted in the United States that described determinants of PIM use in adults ≥60 years of age in a nursing home or residential care facility, in the Emergency Department (ED), or in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 54 publications
6
59
0
2
Order By: Relevance
“…Chronic medication use was higher in the group for whom at least one PIM was continued. As the number of prescribed medications was found to be the main driver of PIM use in earlier studies, these people were likely to use more PIMs.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Chronic medication use was higher in the group for whom at least one PIM was continued. As the number of prescribed medications was found to be the main driver of PIM use in earlier studies, these people were likely to use more PIMs.…”
Section: Discussionmentioning
confidence: 83%
“…With these strengths and limitations in mind, we can identify dispensing of PIMs during well‐defined time periods, and draw cautious, coarse‐grained conclusions regarding their discontinuation. Research has demonstrated that the main determinant of PIM use is the number of prescribed medications, which is probably confounded by the number and type of co‐morbidities . Adding clinical patient data and data on concomitant use of medications and treatment duration would create extensive opportunities for further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done given the substantial changes in the United States healthcare system in the last decade including an increased focus on quality of PIM prescribing following publication of the landmark Institute of Medicine report Crossing the Quality Chasm, revision of the Beers criteria and an increasing focus on quality of care . Studies which exclusively evaluated older adults in the hospital or nursing home were excluded as we have previously published a review of studies in these settings . Studies which used large claims or administrative databases that included inpatient hospital care were included as it was felt that the majority of the included claims were generated by community‐dwelling adults seeking ambulatory care.…”
Section: Methodsmentioning
confidence: 99%
“…The geographic difference by state is common in healthcare. For instance, Gupta et al found a significant difference in patient pain care perception between the states [17], while Nothelle et al reported a difference in potentially inappropriate medication use between US regions [18]. Similarly, Cole, Wilson, and Trivedi reported state variation in quality outcome for community health centers [19].…”
Section: Discussionmentioning
confidence: 99%